A STUDY OF THE INTERACTIONS BETWEEN PLASMA CORTISOL LEVELS, ESTROUS CYCLES, RECTAL TEMPERATURES AND RESPIRATORY RATES IN HEIFERS (1978)
The need to improve the animal protein diet of the Nigerian population has underlined the importation of temperate-evolved cattle into Nigeria. How these animals adapt to the new environment should be of economic and scientific interest. Under the natural hot/humid subequatorial climate of Ibadan, some physiologic, adrenocortical and reproductive functions were investigated in 6 German Brown, 5 Holstein and 6 White Fulani heifers. The Brown/ Holstein and Fulani heifers attained puberty at the average eyes, with the standard deviation, of 17.8 + 1.6, 16.7 + 1.8 and 23.7 + 1.9 months respectively. Observations on estrous cycles showed that estrous period ranged between 7 and 31 hours in the three breeds, the mean values, with the standard errors, being 16.2+0.7, 15.8 ± 0.7 and 14.6 +_0.8 hours in the Brown, Holstein and Fulani heifers respectively. The difference between the Bos taurus and Bos indices cattle was slight but significant. Most estrus commenced during the day with a greater concentration in the morning time. The intensity of estrus was high in both species though, occasionally, a few Fulani heifers showed weaker estrual signs. Average estrous cycle length was slightly longer in the Brown and Fulani than in the Holstein heifers, the values, with the standard errors, being 21.0 + 0.3, 21.4 ± 0.2 and 20.1 + 0.2 days respectively. Ovulations occurred mostly within a day after estrus, and this as well as the duration of estrus and estrous cycle length showed no seasonal variations. There was no indication that Bos taurus and Bos indicus cattle under the semi-intensive management preferred any particular season for increased sexual activity or breeding in the sub-equatorial climate. Marked shifts occurred in the respiratory rates during four selected quarters of the year. Increases occurring in the dry hot season from the values in the relatively cooler season were highly significant. Both mean morning and mean afternoon values (l4 - 44 and 17 – 75 breaths per minute respectively) were highest in the Holstein and lowest in the Fulani heifers. Rectal temperatures showed slight but significant seasonal changes. Mean values were 101.3°F (38.5°C) and 102.2°F (39.0°C) in the morning and afternoon respectively for all the heifers together through the year. The lowest afternoon values occurred in the wettest and coolest months. The Fulani and Holstein heifers showed the lowest and highest mean values respectively. Diurnal and circadian shifts in the respiratory rates and rectal temperatures in the heifers were most exaggerated in the sun and in the Holsteins, the latter particularly exhibited polypnea and hyperthermia. Unlike the zebu, the Bos taurus cattle sought shade in the sun. The Holstein heifers sought shade more frequently and stayed there longer than the Brown heifers. Basal plasma cortisol concentrations at 07 - 08.00 hours, determined by radioimmunoassay during four quarters of the year was low, ranging between 1 - 10 ng/ml with occasional mid-cycle and more frequent- . proestrual and/or estrual elevations. Mean values showed slight but significant seasonal changes. The levels in the dry season were slightly lower than in the wet season. Breed differences were not significant. Diurnal and circadian plasma cortisol concentrations in heifers in the shade and in the sun showed no rhythmical pattern. Exogenous corticotrophin at and after mid-cycle stage elicited marked and prolonged adrenocortical response which varied between heifers, and did not alter estrous. cycle rhythmicity. A high adrenal reserve in the heifers was indicated. Bos taurus cattle have been found to be adaptable to the southern Nigerian climate represented by the Ibadan condition. Management practice should, however, ensure all-year-round provision of shade and adequate nutrition including the adoption of night grazing. The Brown cattle are recommended over the Holsteins because the former are more comfortable, A mixed herd of the two breeds should be discouraged because socially the Browns dominate over the Holsteins. The Fulani cattle are more adaptable to the subequatorial climate than the temperate-evolved cattle as evidenced by the physiological responses, artificial breeding should be suitable for the Fulani cattle as it is for the Bos taurus cattle. The need to adopt better management practices than hitherto existing, range system for the Fulani cattle so that their reproductive and productive attributes may be well manifested, is indicated.